Analisis Penjualan Berdasarkan Pengembangan Konten Media Sosial: Studi UMK Atmosphere Beauty Kota Bukittinggi Pada Media Tiktokshop dan Shopee Tahun 2023 - Rahel Jessica Br Manik; Sampurno Wibowo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In today's social media era, various groups utilize social media for various purposes because it has many benefits. In everyday life, social media is useful as a socialization tool, a source of information, a source of entertainment, a place to channel hobbies, even as an online business platform and promotion. This study aims to measure the sales growth of Atmosphere Beauty products, an MSME in Bukit Tinggi City, West Sumatra, based on content posted on Atmosphere Beauty's TikTok social media. The research method used is a qualitative method by collecting primary and secondary data through interviews, documentation, and observation. In this study, the authors managed to find that the content produced on the TikTok @atmosphere.beauty account refers to three of the four aspects of marketing content, namely education, inspiration, and conversion. The results show that although sales at TikTok Shop are on the rise, Atmosphere Beauty's MSE sales are less than optimal because their TikTok account is less active. The account is only active on Instagram, where they directly include Shopee links for product sales, so Atmosphere Beauty's followers directly access Shopee without going through TikTok Shop.